(untitled) - Kirch, Olaf (USA, 2008)
The LINUX Network Administrators Guide spells out all the information needed for joining a network, whether it's a simple UUCP connection or a full LAN with a Linux system serving as a firewall, an NFS or NIS file server, and a mail and news hub. This book touches on all the essential networking software included with the operating system, plus some hardware considerations. Topics include: Introduction to TCP/IP, Configuring network and serial hardware, Domain Name Service, Serial line communications using SLIP and PPP, NIS and NFS, Taylor UUCP, Administering electronic mail, including sendmail and Exim Administering Netnews, including INN and several news readers, Firewalling using ipfwadm, ipchains, and iptables (netfilter) Masquerading and accounting, IPX configuration for a Novell Netware network.
Keywords: Operating systems (Computers),Hệ thống điều hành (Máy tính)